Antibody-mediated inhibition of the FGFR1c isoform induces a catabolic lean state in Siberian hamsters - Samms, Ricardo J.; Lewis, Jo E.; Lory, Alex; Fowler, Maxine J.; Cooper, Scott; Warner, Amy; Emmerson, Paul; Adams, Andrew C.; Luckett, Jeni C.; Perkins, Alan C.; Wilson, Dana; Barrett, Perry; et al. (Elsevier, 2015)
Hypothalamic tanycytes are considered to function as sensors of peripheral metabolism [1]. To facilitate this role, they express a wide range of receptors, including fibroblast growth factor receptor 1 (FGFR1). Using a monoclonal antibody (IMC-H7) that selectively antagonizes the FGFR1c isoform [2], we investigated possible actions of FGFR1c in a natural animal model of adiposity, the Siberian hamster. Infusion of IMC-H7 into the third ventricle suppressed appetite and increased energy expenditure. Likewise, peripheral treatment with IMC-H7 decreased appetite and body weight and increased energy expenditure and fat oxidation. A greater reduction in body weight and caloric intake was observed in response to IMC-H7 during the long-day fat state as compared to the short-day lean state. This enhanced response to IMC-H7 was also observed in calorically restricted hamsters maintained in long days, suggesting that it is the central photoperiodic state rather than the peripheral adiposity that determines the response to FGFR1c antagonism. Hypothalamic thyroid hormone availability is controlled by deiodinase enzymes (DIO2 and DIO3) expressed in tanycytes and is the key regulator of seasonal cycles of energy balance [3 and 4]. Therefore, we determined the effect of IMC-H7 on hypothalamic expression of these deiodinase enzymes. The reductions in food intake and body weight were always associated with decreased expression of DIO2 in the hypothalamic ependymal cell layer containing tanycytes. These data provide further support for the notion the tanycytes are an important component of the mechanism by which the hypothalamus integrates central and peripheral signals to regulate energy intake and expenditure.